“Nothing about Us without Us”: Sex Workers’ Informal Political Practices in Ukraine - Rachok, Dafna (Anthropologica, 2020)
How do vulnerable populations engage with politics? And what does politics mean to them? Building on four months of ethnographic fieldwork and 15 semistructured interviews with sex workers in Kropyvnyts’kyi, Ukraine, I show how informal political practices are employed by marginalised groups like sex workers to promote their agenda of the normalisation of sex work. Examining sex workers’ activism in Ukraine through empowerment strategies and resistance politics, I enquire about formal and informal political strategies that sex workers resort to, how these strategies are used, and whether informal political practices can lead to the community’s empowerment. With a focus primarily on street sex workers who are engaged in community organisation, I show how a controversial topic such as sex can be utilised by sex workers to attract attention to their marginalised situation and politicise their activism. Complicating the discussion of politics and political participation by viewing it through the lens of feminist anthropology, this paper attempts to contribute to the discussion about women’s empowerment and to expand the category of “political practice” and “political activism.” This paper concludes that Kropyvnyts’kyi sex workers often resort to small-scale political tactics in order to probe the limits of political possibility.